The Legends of the Saints in Old Norse-Icelandic Prose. - Wolf, Kirsten (Toronto Old Norse-Icelandic Series (TONIS), 2013)
With The Legends of the Saints in Old Norse-Icelandic Prose, Kirsten Wolf has undertaken a complete revision of the fifty-year-old handlist The Lives of the Saints in Old Norse Prose.